An analysis of the effects of management accounting services on the financial performance of SME: The moderating role of information technology - Emmanuel Gyamera; Williams Abayaawien Atuilik; Ivy Eklemet; Akwetey Henry Matey; Lexis Alexander Tetteh; Paul Kwasi Apreku-Djan (Cogent Business & Management, 2023)
Management accounting is very important in the field of accounting. It is a subject which implementation can bring about firm development. There are a lot of studies about management accounting. Past research have analysed various aspects of management accounting. However, the effect of management accounting services on the financial performance of SMEs have not been deeply researched into. This study aims to fill this gap by analysing the effect of management accounting service on the financial performance of SMEs in Ghana's commerce, service, and manufacturing industries. The study's population comprises registered SMEs from the Registrar General's Department. The sample size was calculated using a population of 4,000 registered small and medium businesses to arrive at 365 SMfomular. Managers of SMEs were chosen and contacted using a systematic sample process and given questionnaires to complete. This study used the agency theory and Technology Acceptance Model (TAM). The PLSSEM Software was used to analyze the data collected from the respondents. The study found a relationship between SMEs' performance and management accounting methods.
Keywords: 650; financial performance; information technology; management accounting services (MAS); small and medium scale enterprise (SME)